Comparison of some characteristics of charged pions in p12C and n12C collisions at 4.2 GeV/c - Bekmirzaev, Rahmatulla; Bekmirzaeva, Xursanoy; Olimov, Khusniddin; Mustafaeva, Marjona (Физико-технологического образование, 2021)
The new experimental data on various characteristics of the secondary charged pions produced in n12C collisions at 4.2 GeV/c are presented. A comparative analysis of the average multiplicities and various kinematic characteristics of the charged pions produced in n12C and p12C collisions at 4.2 GeV/c is made. The experimental data are compared systematically with the predictions of the modified FRITIOF model